Abnormal Cerebral Blood Flow and Functional Connectivity Strength in Subjects With White Matter Hyperintensities - Huang, Hao; Zhao, Kun; Zhu, Wenzhen; Li, Hui; Zhu, Wenhao (Frontiers in Neurology, 2021)
White matter hyperintensities (WMH) are common neuroimaging findings in the aging population and are associated with various clinical symptoms, especially cognitive impairment. Abnormal global cerebral blood flow (CBF) and specific functional connections have been reported in subjects with higher WMH loads. Nevertheless, the comprehensive functional mechanisms underlying WMH are yet to be established. In this study, by using combining resting-state functional MRI (fMRI) and arterial spin labeling (ASL), we investigated the neurovascular dysfunction in subjects with WMH in terms of CBF, functional connectivity strength (FCS) and CBF-FCS coupling. The whole-brain alterations of all these measures were explored among non-dementia subjects with different WMH loads using a fine-grained Human Brainnetome Atlas. In addition, exploratory mediation analyses were conducted to further determine the relationships between these neuroimaging indicators, WMH load and cognition. The results showed that subjects with higher WMH loads displayed decreased CBF and FCS mainly in regions involving the cognitive- and emotional-related brain networks, including the default mode network (DMN), salience network (SN) and central executive network (CEN). Notably, subjects with higher WMH loads also showed an abnormal regional CBF-FCS coupling in several regions of the thalamus, posterior cingulate cortex and parahippocampal gyrus involving the DMN. Furthermore, regional CBF in the right inferior temporal gyrus and right dorsal caudate may mediate the relationship between WMH load and cognition in WMH subjects. These findings indicated characteristic changes in cerebral blood supply, brain activity and neurovascular coupling in regions involving specific brain networks with the development of WMH, providing further information on pathophysiology underpinnings of the WMH and related cognitive impairment.